PENGARUH LATIHAN REVERSE BODY LIFTS TERHADAP KEKUATAN OTOT PUNGGUNG ATLET KADET PUTRA GULAT RIAU - Denis Diva Jordan Lb. Batu; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the observations of research at PPLP Gulat Dispora Riau and the results of interviews with coach Yudha Setia Nugraha where the male cadet athletes of Riau wrestling aged 15-17 years have a deficiency which is influenced by one of the factors of physical condition, namely strength, where when carrying out leg attacks the strength of the back muscles not strong so that the opponent can anticipate by pressing his body down, wrestlers also find it difficult to lift the opponent that hit his body, and difficulty lifting the opponent's leg when standing. The title that the research examined was "the effect of reverse body lifts training on the back muscle strength of the Riau wrestling male cadet athletes" so the aim of this research was to determine the effect of reverse body lifts on the back muscle strength of the male cadets in Riau wrestling. The form of this research is (one group pretest-postest design) with a population of male cadet athletes in Riau wrestling. The data in this research were the entire population, amounting to 6 people. The instrument used in this research is to use a back and leg dynamometer, which aims to determine how much influence the athlete's back muscle strength is. The results obtained were analyzed using the t-test which resulted in a t count of 33.673 with a t table of 1.943, so Ha was accepted, at the alpha (α) 0.05 level. It can be concluded that there is an effect of reverse bpdy lift training on the back muscle strength of male cadet athletes in Riau wrestling.Key Words: Reverse Body Lifts Exercise, back muscle strength